INTEGRASI KURIKULUM PESANTREN DAN MADRASAH ALIYAH - Ishak, Ahmad; Mahmud, Hasibuddin; Rosmiati, Rosmiati; Wahab, Abdul (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhamamdiyah Palopo, 2024)
The integration of the madrasah aliyah curriculum and the ma'had curriculum is aimed at producing better educational outputs, namely being able to master madrasahan and pesantren. The curriculum in ma'had complements the curriculum in madrasah aliyah and also linguistics. Because the educational process in this institution, in addition to aiming to master the science of madrasahan and pesantren, also leads to the ability to master three languages, namely Arabic, English, and Japanese Each of these sciences is very important to be mastered by students with the hope that students will be able to socialize with society in the current era of globalization Integration of MA curriculum and Islamic Boarding School curriculum at Hasan Yamani Polewali Mandar Islamic Boarding School (2) To find out how the implementation of the integration of the Madrasah Aliyah curriculum and Hasan Yamani Polewali Mandar Islamic Boarding School. To discuss these problems, researchers use a qualitative approach. Data collection techniques used in this study are observation, interviews and documentation. The source of the data was obtained from the principal, and MA teacher Sheikh Hasan Yamani. The data processing process is carried out through three stages, namely: data reduction, data presentation (data display), and verification / conclusion / conclusion. The results showed that: 1) The integration of the pesantren curriculum in the Islamic boarding school of Sheikh Hasan Yamani in its application is to insert pondok (pesantren) material into madrasah learning hours. Students in one day during school hours learn madrasah subject matter and cottage material. 2) Sheikh Hasan Yamani Islamic Boarding School is one of the Islamic boarding schools that integrates the madrasah curriculum which in this case MTs and MA with the pesantren curriculum. In the pesantren curriculum, Sheikh Hasan Yamani Islamic Boarding School adopts the Kuliyat al-Mu‟allimin al-Islamiyyah (KMI) curriculum of the Modern Islamic Boarding School Darussalam Gontor Ponorogo